Lifestyle factors including less cutaneous sun exposure contribute to starkly lower vitamin D levels in U.K. South Asians compared with the white population. (December 2013) - Kift, R.; Berry, J.L.; Vail, A.; Durkin, M.T.; Rhodes, L.E.; Webb, A.R.
<x xml:space="preserve">Abstract</x> What's already known about this topic? South Asians in the U.K. have much lower vitamin D levels than the white population. What does this study add? Behavioural factors significantly contribute to lower vitamin D status, with lower ultraviolet exposure, dietary intake and supplement use contributing. The behavioural data suggest more targeted health messages are needed to address the vitamin D status of the U.K. South Asian population.